Analysis of Earthquake Vulnerability with an Emphasis on Providing Optimal Locating Pattern of Special Land Uses (Health , Medical Services and Educational Centers) Case study: Tabriz Worn Textures - Dr. Issa Ebrahimzadeh; Shamsollah Kazemizad; Hakimeh Ghanbari (جغرافیا و آمایش شهری منطقه‌ای, 2012)
Although at the present, it is not possible for human to prevent earthquake, but the society's preparedness to face with this natural phenomenon, is the most important factors in reducing the damages caused by the earthquake. One of the special measures for reducing the earth quake damages in the cities is the optimal locating of land uses. If the urban land uses are being located precisely, there will be a great save in the costs including health costs and time. According to the estimates, one fifth of the total area of Tabriz city have been occupied by worn out tissues and according to the latest estimates, about 400 to 500 thousand people of Tabriz citizens reside in these areas, and  in case of  earthquake occurrence in Tabriz, a very destructive disaster will occur in these areas.This study has been performed by using criterion - analytical model and to the aim of presenting optimum locating of special usages for mitigating the damages due to earthquake in part of Tabriz worn out texture by the method of network analysis and AHP model in GIS environment. Studies show that in the under study area, there is no strong buildings, it has lack of  proper planning with very narrow and low width passages , which in zoning of Tabriz fault risk in the land uses of this city, it is located in the areas with high vulnerability and risk due to the damages of earth quake . The results indicate that a large part of the study area in spite of high population density, construction, educational, commercial and etc., are outside of the function scope of the existing particular land uses, which have a great vulnerability against the earthquake risks. This situation, itself is the reason  of the  lack of specific users needed to provide full coverage of the under study space, So that in the conditions of earthquake occurrence, for emergency services and temporary housing in fact  half of this area will have no access to a specific land use. In this case, the need to locate and deploy the new land use is being felt more than before. Therefore, for mitigating the damages caused by earthquakes in this area, using the results of network analysis and AHP, locating, new educational, health and treatments uses were proposed.